Effects of dyadic-based physical activity intervention on cancer-related fatigue among cancer survivors: A scoping review - Song, Dongyu; Liu, Yuzhou; Lai, Claudia K. Y.; Li, Yuli (Frontiers in Psychology, 2023)
Objective: Cancer-related fatigue is one of the most common adverse reactions to cancer survivors, which has a significant impact on the daily life. As a traumatic event, cancer not only brings great physical and mental pain to patients, but also poses a threat to the physical and psychological health of caregivers. Current studies have shown that physical activity improves cancer-related fatigue in cancer survivors. And studies have suggested that dyadic interventions are more effective in improving patient outcomes and may also provide some benefits to caregivers. But the literature on the effects of dyadic-based physical activity on improving cancer-related fatigue has not been synthesized. This scoping review described the scope and impact of studies on cancer-related fatigue with dyadic-based physical activity interventions. Methods: Six databases which is PubMed, Cochrane Library, Web of Science, Embase, CINAHL and Medline were searched for all studies of dyadic-based physical activity interventions with outcome measures including cancer-related fatigue published since the inception of the databases through May 2022. The search strategy was developed based on PICO principles. Results: This article includes 6 pre and post-test designs and 2 randomized controlled trial design. The majority of participants were survivors with breast and lung cancer. The overall results showed that the effectiveness of dyadic-based physical activity interventions in improving cancer-related fatigue was unsatisfactory. Conclusions: This scoping review suggests that current dyadic-based physical activity interventions are not well researched among cancer survivors. In the future, more high-quality studies with more sophisticated and rigorous interventions are needed. Keyword